Evaluating sex as a predictive marker for response to bevacizumab in metastatic colorectal carcinoma: Pooled analysis of 3, 369 patients in the ARCAD database. (January 2023) - Margalit, Ofer; Harmsen, William S.; Shacham-Shmueli, Einat; Voss, Molly M.; Boursi, Ben; Wagner, Anna D.; Cohen, Romain; Olswold, Curtis L.; Saltz, Leonard B.; Goldstein, Daniel A.; Hurwitz, Herbert; Tebbutt, Niall C.; et al.
Abstract: Background: Previous studies suggest a possible sex-specific response to bevacizumab in metastatic colorectal carcinoma (mCRC), showing a benefit in males, while the effect in females is less significant. Methods: Data from 3369 patients with mCRC enrolled on four first-line randomised trials testing chemotherapy with or without bevacizumab (2000–2007) were pooled. Association between sex and progression-free survival and overall survival (OS) was evaluated by stratified Cox regression model, adjusted for potential confounders. Predictive value was evaluated by interaction effect between sex and treatment. In a pre-planned secondary analysis, analyses were stratified using an age cut point of 60 years to evaluate the possible role of menopausal-related effects. Results: Bevacizumab was associated with an improved median OS in males and females, with a 2.3- and 0.6-months benefit, respectively. Stratified by age, bevacizumab resulted in improved OS in males at both age categories. In females at or above the age of 60 (n = 731), bevacizumab resulted in improved OS. However, in females below the age of 60 (n = 634), OS benefit did not reach statistical significance (adjusted hazard ratio = 0.94, 95% confidence interval 0.74–1.20). Conclusions: Our results confirmed the OS benefit from the addition of bevacizumab to first-line chemotherapy in mCRC in both sexes. Among females, the benefit was less than 1 month. For females under the age of 60, there was no survival benefit. These findings could be used to relieve financial toxicity or be redistributed within healthcare systems for other health-related purposes. Highlights: Bevacizumab was associated with an improved median overall survival (OS) of 1.8 months. For females, median OS benefit from bevacizumab was <1 month. For females under the age of 60, there was no OS benefit. Sex- and age-specific reporting is essential in future trials testing bevacizumab.